Statistical optimization of process parameters for landfill leachate treatment using electro-Fenton technique - M.H.,, Isa (2010)

(untitled)
Mature landfill leachate is typically non-biodegradable and contains high concentration of refractory organics. The aim of this research was to optimize operating parameters in electro-Fenton process, for the removal of recalcitrant organics from semi-aerobic landfill leachate using response surface methodology (RSM). Effectiveness of important process parameters H2O2/Fe2+ molar ratio, current density, pH and reaction time were determined, optimized and modeled successfully. Significant quadratic polynomial models were obtained (R2 = 0.9972 and 0.9984 for COD and color removals, respectively). Numerical optimization based on desirability function were employed; in a 43 min trial 94.07% of COD and 95.83% of color were removed at pH 3 and H2O2/Fe2+ molar ratio 1, while current density was 49 mA/cm2. The results indicate that E-Fenton process was an effective technology for semi-aerobic landfill leachate treatment. Â© 2009 Elsevier B.V. All rights reserved.